Copeptin as a Prognostic Marker in Acute Chest Pain and Suspected Acute Coronary Syndrome. (24th January 2018) - Morawiec, Beata; Kawecki, Damian; Przywara-Chowaniec, Brygida; Opara, Mariusz; Muzyk, Piotr; Ho, Lam; Tat, Lui Chun; Gabrysiak, Artur; Muller, Olivier; Nowalany-Kozielska, Ewa
Abstract : Background . In patients admitted with chest pain and suspected acute coronary syndrome (ACS), it is crucial to early identify those who are at higher risk of adverse events. The study aim was to assess the predictive value of copeptin in patients admitted to the emergency department with chest pain and nonconclusive ECG. Methods . Consecutive patients suspected for an ACS were enrolled prospectively. Copeptin and high-sensitive troponin T (hs-TnT) were measured at admission. Patients were followed up at six and 12 months for the occurrence of death and major adverse cardiac and cerebrovascular events (MACCE). Results . Among 154 patients, 11 patients died and 26 experienced MACCE. Mortality was higher in copeptin-positive than copeptin-negative patients with no difference in the rate of MACCE. Copeptin reached the AUC 0.86 (0.75–0.97) for prognosis of mortality at six and 0.77 (0.65–0.88) at 12 months. It was higher than for hs-TnT and their combination at both time points. Copeptin was a strong predictor of mortality in the Cox analysis (HR14.1 at six and HR4.3 at 12 months). Conclusions . Copeptin appears to be an independent predictor of long-term mortality in a selected population of patients suspected for an ACS. The study registration number isISRCTN14112941 .